A Computational and Structural Database Study of the Metal-Carbene Bond in Groups IA, IIA, and IIIA Imidazol-2-Ylidene Complexes. (24th December 2019) - Tetteh, Samuel
Abstract : Imidazol-2-ylidenes are important N-heterocyclic carbenes which have become universal ligands in organometallic and coordination chemistry. Generally classified as σ -donor ligands, these compounds have been used to stabilize various metal complexes which hitherto were less stable in their catalytic processes. Herein, the number and distribution of group IA, group IIA, and group IIIA metal-imidazol-2-ylidene complexes retrieved from the Cambridge Structural Database (CSD) are assessed. The data showed that the mean M-Ccarbene bond length increases with increasing ionic size but is similar across each diagonal. Dominant factors such as Lewis acidity and electrostatic attractions were found to control the bonding modes of the respective ions. Generally, the metal ions show preference for tetrahedral coordination with larger cations forming complexes with higher coordination numbers. For their high number of entries (101), tetrahedrally coordinated boron complexes with various electron withdrawing and electron donating groups were studied computationally at the DFT/B3LYP level of theory. The strength of the B-Ccarbene bond was found to depend on steric interactions between bulky groups on the borenium atom and substituents on the N-positions of the imidazol-2-ylidene ligand. This observation was further confirmed by estimation of the binding energy, natural charge, and the electron distribution in the B-Ccarbene bond.